Triggers of stress cardiomyopathy and their association with clinical outcomes. (25th November 2020) - Chiu, S; Nayak, R; Duan, L; Shen, A; Lee, M
Abstract: Background: Stress cardiomyopathy can be a result of physical stress, emotional stress, or both. Whether the type of trigger affects clinical outcomes is not well studied. Purpose: The objectives of this study were to identify the prevalence of emotional and physical stressors and to assess differences in patient characteristics and mortality based on the type of trigger. Methods: We conducted a retrospective review of 523 consecutive patients who presented to our institution from 2006 to 2016. All patients presented with acute coronary syndrome. Triggers for stress cardiomyopathy were abstracted from reviewing patients' medical records. Patients were categorized into those with 1) physical trigger, 2) emotional trigger, 3) both physical and emotional trigger, or 4) no known trigger. Baseline characteristics and clinical outcomes were reported. Results: Among 523 patients with stress cardiomyopathy, 151 (28.9%) had a physical trigger, 189 (36.1%) had an emotional trigger, 30 (5.7%) had both physical and emotional triggers, and 153 (29.3%) had no known triggers identified. Men comprised the higher proportion of patients with physical triggers. Comorbidities including diabetes, pulmonary disease, chronic kidney disease and hypothyroidism were more prevalent among patients with physical triggers. Compared to patients with no obvious triggers, patients with a physical trigger had a much higher mortality rate (hazard ratio 2.0, 95% CI 1.2–3.3, p=0.007), whereas patients with an emotional trigger had significantly lower mortality (hazard ratio 0.40, 95% CI 0.21–0.89, p=0.007). Conclusion: Different triggers for stress cardiomyopathy is associated with different baseline characteristics and clinical outcomes. Overall survival is worst in the group with an identified physical trigger. Funding Acknowledgement: Type of funding source: None